Expression of Dopamine D1−4 and Serotonin 5-HT1A-3A Receptors in Blood Mononuclear Cells in Schizophrenia - Wysokiński, Adam; Kozłowska, Elżbieta; Szczepocka, Ewa; Łucka, Anna; Agier, Justyna; Brzezińska-Błaszczyk, Ewa; Sobierajska, Katarzyna (Frontiers in Psychiatry, 2021)
Introduction: The aim of this study was to determine the mRNA expression profile of dopamine D1, D2, D3, D4 and serotonin 5-HT1A, 5-HT2A and 5-HT3A receptors in peripheral blood mononuclear cells (PBMCs) in schizophrenia and the in vitro effect of antipsychotics on the expression of these receptors in PBMCs of healthy subjects. Materials and methods: Twenty-seven patients with schizophrenia and 29 healthy controls were recruited for the study. All study subjects underwent thorough clinical assessment, including anthropometric and body composition measurements. The expression of mRNA for dopamine D1-4 and serotonin 5-HT1A-3A receptors was measured using quantitative RT-PCR in peripheral blood mononuclear cells. In vitro mRNA and protein expression of these receptors was measured using quantitative RT-PCR and Western Blotting in PBMCs cultured with quetiapine, haloperidol, aripiprazole, risperidone, olanzapine or clozapine at IC50, half of IC50 and one-quarter of IC50 concentrations. Results: The key finding was that the schizophrenia group demonstrated significantly higher mRNA expression of D1, D2 and D4 receptors (p <0.001), and significantly lower mRNA expression of 5-HT3A receptors (p <0.01). After adjusting for smoking, the mRNA expression of D1 lost its significance, while that of D3, 5-HT1A, 5-HT2A became significant (all three were lower in the schizophrenia group). These receptors also demonstrated different ratios of mRNA expression in the schizophrenia group. The in vitro experiments showed that high concentrations of antipsychotics influenced the mRNA and protein expression of all studied receptors. Conclusion: Schizophrenia patients display a distinctive pattern of dopamine and serotonin receptor mRNA expression in blood mononuclear cells. This expression is little affected by antipsychotic treatment and it may therefore serve as a useful diagnostic biomarker for schizophrenia.